2016
DOI: 10.1071/rd14086
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene-expression profiles from canine cumulus cells of ovulated versus in vitro-matured oocytes

Abstract: We compared the nuclear maturation status and gene-expression profiles of canine cumulus cells (CCs) derived from cumulus-oocyte complexes (COCs) that were spontaneously ovulated versus those that were matured in vitro. Cumulus-oocyte complexes were retrieved from uteri by surgical flushing (after spontaneous ovulation) or by ovariectomy follicle aspiration and in vitro maturation. The objective of Experiment 1 was to investigate the nuclear maturation status of in vivo- versus in vitro-matured oocytes. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
4
3
0
Order By: Relevance
“…GJA1, or connexin 43, has been proposed as a major mediator of cell-cell communication via gap junctions (Gittens and Kidder 2005) and has been identified as a non-invasive biomarker for the fertilisation potential of human oocytes (Feuerstein et al 2007;Hasegawa et al 2007). The findings of the present study show that Gja1 expression was significantly lower CCs surrounding in vivo-matured MII oocytes than in CCs enclosing immature or IVM oocytes, supporting previous results obtained in the bovine (Calder et al 2003), canine (Cho et al 2016) and in humans (Li et al 2015). The reduced expression of GJA1 in CCs after oocyte maturation is beneficial (Edry et al 2006) because it is related to cumulus expansion and decreased diffusion of cAMP and cGMP from the CCs to the oocyte, which is followed by the end of meiotic arrest and extrusion of the first polar body (Shao et al 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…GJA1, or connexin 43, has been proposed as a major mediator of cell-cell communication via gap junctions (Gittens and Kidder 2005) and has been identified as a non-invasive biomarker for the fertilisation potential of human oocytes (Feuerstein et al 2007;Hasegawa et al 2007). The findings of the present study show that Gja1 expression was significantly lower CCs surrounding in vivo-matured MII oocytes than in CCs enclosing immature or IVM oocytes, supporting previous results obtained in the bovine (Calder et al 2003), canine (Cho et al 2016) and in humans (Li et al 2015). The reduced expression of GJA1 in CCs after oocyte maturation is beneficial (Edry et al 2006) because it is related to cumulus expansion and decreased diffusion of cAMP and cGMP from the CCs to the oocyte, which is followed by the end of meiotic arrest and extrusion of the first polar body (Shao et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Paradoxically, in the present study we found that Gapdh mRNA transcripts decreased slightly in CCs after in vivo maturation compared with CCs from immature GV oocytes. These differences between experimental groups dissuaded us from using this gene as an internal control in the quantitative analysis of gene expression, in contrast with previous reports in dogs (Cho et al 2016), mice (Shao et al 2015) and humans (Ouandaogo et al 2012), but support previous findings in rabbit embryos (Arias-Á lvarez et al 2013a(Arias-Á lvarez et al , 2013b, mouse oocytes (Jeong et al 2005;Cui et al 2007) and bovine oocytes (Bermejo-Á lvarez et al 2010;Adona et al 2016). These controversial results indicate that the expression of GAPDH could differ among species and this deserves further investigation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The expression of the cumulus expansion-related transcripts GDF-9 and BMP-15 was studied in canine CCs using nonmatured COCs and IVM COCs. The gene expression of these paracrine factors found in CCs in this work was previously reported in canine ovaries [25,27], as in other animal species [28,29]. The expression levels of these transcripts in CCs were stage dependent over the estrous cycle, which was in agreement with our previous studies performed in canine oocytes and granulosa/theca cells ex vivo [25].…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported in rodents that antibodies to members of TGF‐1 family prevented development effects of oocytes and cumulus cells in vitro (Vanderhyden, Macdonald, Nagyova, & Dhawan, ). The expression of these two genes (Palomino & De los Reyes, ), and their encoded proteins GDP‐9 and BMP‐15 (Fernandez et al, ; Maupeu et al, ) during the follicular development and IVM (Cho et al, ; De los Reyes et al, ), has been previously reported in canines. Therefore, the addition of antibodies against both proteins in vitro was conducted to explore the influence of intrinsic GDF‐9 and BMP‐15 on nuclear maturation in this species.…”
Section: Discussionmentioning
confidence: 96%